Principles of macroeconomics - Gottheil, Fred M (Ohio South-Western College Publishing, 1999)
This book presents Macro economic theory in the economy without a Government or Foreign sector. This simplifies the analysis. This book is written for students not for professor. This volumes covers the topics of economic analysis, employment inflation an
Keywords: Macroeconomics; Fiscal policy; Monetary policy; Competition, International